Komparatif Analisis Keamanan Aplikasi Instant Messaging Berbasis Web - Imam Riadi; Rusydi Umar; Muhammad Abdul Aziz (Ikatan Ahli Informatika Indonesia (IAII), 2020)
Web-based instant messaging applications vulnerability has become one of the main concerns for its users in line with the increasing number of cybercrimes that occur on social media. This research was conducted to determine the comparability of the vulnerability value of the web-based WhatsApp, Telegram, and Skype applications using the Association of Chief Police Officers (ACPO) method. Digital artifacts in the form of text messages, picture messages, video messages, telephone numbers, and user IDs have been acquired in this research process using FTK imager and OSForensic tools. The results of the study using the FTK imager and OSForensic tools show that the web-based Skype application has a vulnerability value of 92%, while WhatsApp and Web-based Telegram have the same vulnerability value with 67% each based on all digital artifacts that successfully acquired.